Digital Marketing Strategy through Instagram in Payakumbuah Padang Restaurant - Rifqi Zain; Jati Paras Ayu (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2025)
The development of digital marketing has had a significant impact on business marketing strategies, especially in the culinary sector. This research aims to analyze digital marketing promotion strategies through Instagram implemented by the Padang Payakumbuah Restaurant owned by Arief Muhammad. This research method uses a qualitative approach with data collection in the form of interviews with the management and observations of the Instagram content @padangpayakumbuah. The research findings explain that the digital marketing strategy implemented by Padang Payakumbuah focuses on three aspects: Search Engine Optimization (SEO), Social Media Content, and Quoting. SEO optimization through Google Business and social media can enhance the visibility and the number of visitors to the restaurant. The utilization of engaging and unique content on social media has successfully built engagement and strengthened brand awareness for Padang Payakumbuah. Furthermore, the use of quoting in captions and customer reviews plays a role in establishing trust and consumer loyalty.The digital marketing strategy through Instagram can be considered successful in increasing brand exposure and customer engagement for Padang Payakumbuah. Suggestions for further development include strengthening interactions with followers, conducting regular performance analyses, and implementing customer loyalty programs to maintain competitiveness in the culinary industry.